Molecular Signaling of Progesterone, Growth Hormone, Wnt, and HER in Mammary Glands of Dogs, Rodents, and Humans: New Treatment Target Identification - Timmermans-Sprang, Elpetra P. M.; Gracanin, Ana; Mol, Jan A. (Frontiers in Veterinary Science, 2017)
Mammary tumors are the most common form of neoplasia in the bitch. Female dogs are protected when they are spayed before the first estrus cycle, but this effect readily disappears and is already absent when dogs are spayed after the second heat. As the ovaries are removed during spaying, ovarian steroids are assumed to play an essential role in tumor development. The sensitivity towards tumor development is already present during early life which may be caused by early mutations in stem cells during the first estrus cycles. Later on in life tumors arise that are mostly steroid receptor positive, although a small subset of tumors overexpressing HER2 and some lacking ER, PR and HER (triple negative) are present, as is the situation in humans. Progesterone, acting through progesterone receptors, is the major steroid involved in outgrowth of mammary tissue. Progesterone receptors (PR) are expressed in two forms, the PRA and PRB isoforms derived from splice variants from a single gene. The dog, and the whole family of canids, have only a functional PRA isoform whereas the PRB isoform, if expressed at all, is devoid of intrinsic biological activity. In human breast cancer overexpression of the PRA isoform is related to more aggressive carcinomas making the dog a unique model to study PRA related mammary cancer. Administration of progesterone to adult dogs results in local mammary expression of growth hormone (GH) and Wnt4. Both proteins play a role in activation of mammary stem cells. In this review we summarize what is known on progesterone, GH and Wnt signaling in canine mammary cancer, how the family of HER-receptors could interact with this signaling, and what this means for comparative and translational oncological aspects of human breast cancer development.